2006
DOI: 10.1007/s11062-006-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between level of aggressiveness of personality and characteristics of EEG frequency components

Abstract: In a group of 80 adults of both sexes, we studied the correlation between the characteristics of aggressiveness of the individual (diagnosed using the Buss-Durkee questionnaire) and parameters of the frequency components (rhythms) of EEG recorded in the resting state from leads C3 and С4 according to the 10-20 system. Despite the natural high interindividual variability, the higher spectral powers of nearly all EEG frequency components (δ-, θ-, α-, and β rhythms) and coefficient of reactivity of the α rhythm c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A number of the findings related to this statement were reviewed in our previous paper [1]. Here, some additional facts are described, which are also interesting from the above aspect.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A number of the findings related to this statement were reviewed in our previous paper [1]. Here, some additional facts are described, which are also interesting from the above aspect.…”
Section: Discussionmentioning
confidence: 71%
“…The differential/psychophysiological aspect of this problem makes it necessary to thoroughly examine the objective correlates of this feature of personality. In our earlier paper [1], we reported that the level of aggressiveness of the personality (measured using the Buss-Durkee inventory) demonstrates negative correlations with spectral powers of nearly all frequency components of the background EEG.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation